PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA TENAGA PENJUAL MELALUI KOMITMEN ORGANISASI - -, Mahmud -; Wibowo, Wahyu -; -, Samiadji - (Manajemen & Bisnis Jurnal, 2015)
Abstract. PT Tupperware Indonesia, a manufacturer of home appliances, became the fourth largest contributor to the total sales of Tupperware products around the world. Sales of Tupperware products in East Java in the first half of 2010 in the East Java market grew 50%. PT Tupperware product sales figures. Margo Pangestu Mighty Malang fluctuated, Tupperware sales in 2010-2011 experienced a large increase compared to the previous year's sales, although the prices offered by the Tupperware is quite expensive when compared with Lion Star products are becoming a major competitor, it does not affect the customer to remain loyal using products from Tupperware. Sales growth in Malang PT indicates sales force. Margo Pangestu Perkasa has good sales performance. These conditions did not dampen the PT. Margo Pangestu Mighty conduct a thorough reform of the management of human resources (HR). The purpose of this study was to analyze the influence of leadership style and work motivation on organizational commitment and performance sellers. The sample in this study was 57 salesperson (manager). The analysis tool is used path analysis. Based on the analysis found evidence that the leadership style and work  motivation and organizational commitment affect the performance of the seller. Organizational commitment may mediate the effect of leadership style and work motivation on the performance of salespeople. To improve the performance of salespeople, leaders of PT. Margo Pangestu Mighty, need to implement a style of leadership by providing work guidance to do the job to the salesperson (manager) in order to encourage increased organizational commitment. Salesperson (manager), in implementing targeted sales need to gain the support of fellow co-workers so as to sales targets set gill  Keywords: leadership style, employee motivation, organizational commitment, and performance of salespeople